Investigating English Target And Learning Needs: A Study Of Petroleum Engineering Students At Hadramout University Of Sciences And Technology - Al-Tamimi, Atef Saleh Habshan (2010)

(untitled)
The purpose of the current research is to investigate the English target and learning needs of petroleum engineering students at Hadramout University of Sciences and Technology (HUST), Yemen. Guided by Hutchinson and Waters’s (1987) target and learning needs framework, students’ English language and communication skills needs are identified in terms of necessities, lacks and wants. For the learners’ English learning needs, the study includes their motivation and attitudes towards learning the English language, their learning styles preferences (LSPs), teaching styles, teaching methods and techniques and preferences of the English language course. To synthesise the conceptual framework, methods, approaches, ways and/or ideas are adopted from a number of theories, models and studies, which are related to the issues of interest in the current needs analysis (NA) study.